2013
DOI: 10.1017/s1461145713000606
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical models of antipsychotic drug action

Abstract: One of the main obstacles faced by translational neuroscience is the development of animal models of psychiatric disorders. Behavioural pharmacology studies indicate that psychedelic drugs, such as lysergic acid diethylamide (LSD) and dissociative drugs, such as phencyclidine (PCP), induce in healthy human volunteers psychotic and cognitive symptoms that resemble some of those observed in schizophrenia patients. Serotonin 5-HT2A and metabotropic glutamate 2 receptors have been involved in the mechanism of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 181 publications
1
28
0
Order By: Relevance
“…Although there exists wide evidence relating schizophrenia and dopamine function, as discussed in different sections of the present work and in part of the cited literature, an outstanding example of a combined genetic, neurobehavioral and pharmacological approach leading to the discovery of new neurochemical mechanisms with great potential relevance for schizophrenia is provided by recent work from Gonzalez-Maeso's group and others (e.g. [5]- [7] [13]). These authors have demonstrated that 5-HT2A and mGluR2 cortical (prefrontal) receptors form a physical functional complex (named 5HT2AR/mGluR2 complex), which is related to several schizophrenic symptoms in mice (they have used 5-HT2A and mGluR2 knockout mice), to hallucinogenic drug effects and to atypical antipsychotic drug therapeutic actions.…”
Section: The Roman High-avoidance (Rha) and Low-avoidance (Rla) Rat Lmentioning
confidence: 88%
See 2 more Smart Citations
“…Although there exists wide evidence relating schizophrenia and dopamine function, as discussed in different sections of the present work and in part of the cited literature, an outstanding example of a combined genetic, neurobehavioral and pharmacological approach leading to the discovery of new neurochemical mechanisms with great potential relevance for schizophrenia is provided by recent work from Gonzalez-Maeso's group and others (e.g. [5]- [7] [13]). These authors have demonstrated that 5-HT2A and mGluR2 cortical (prefrontal) receptors form a physical functional complex (named 5HT2AR/mGluR2 complex), which is related to several schizophrenic symptoms in mice (they have used 5-HT2A and mGluR2 knockout mice), to hallucinogenic drug effects and to atypical antipsychotic drug therapeutic actions.…”
Section: The Roman High-avoidance (Rha) and Low-avoidance (Rla) Rat Lmentioning
confidence: 88%
“…While behavioral tests/models, drug-and lesion-induced models, developmental models and mouse genetic models have been thoroughly discussed in recent reviews (e.g. [1]- [3] [9] [10] [13] [17] [19]), genetically-based rat models have received very little attention. Thus, the aim of the present review is to discuss the most relevant aspects of some genetic approaches that have used selective breeding of rats to model schizophrenia-relevant features, as well as to describe other approaches based on existing rat strains (either selectively bred or not) which present behavioral and/or neurobiological profiles relevant to the disorder.…”
Section: Genetic Rat Models Of Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the in vitro pharmacological profiles, compound 3 and these 6 analogs were then subjected to in vivo behavioral studies to verify their effects on schizophrenia Antipsychotic efficacy is usually assessed by the phencyclidine (PCP)-induced hyperactivity model [49][50] . PCP, an N-methyl-D-aspartic acid receptor (NMDAR) antagonist, has been found to simulate schizophrenia 51 , and in rodents, this effect can be reversed by antipsychotic drugs 52 . Then the antipsychotic activities of the above 7 compounds were studied in the PCP-induced locomotor hyperactivity test in ICR mice ( Figure S6).…”
Section: In Vivo Behavioral Evaluation Of the Selected Compoundsmentioning
confidence: 99%
“…2) Are PSD transcripts' expression differently affected in Ddo −/− vs. Ddo +/+ mice after administration of phencyclidine (PCP), a widely used model of aberrant glutamate transmission considered to mimic several aspects of schizophrenia (Moreno and Gonzalez-Maeso, 2013)? In this latter model, we also studied modifications in ataxia, a well known effect of NMDAR blockade by PCP (Enomoto et al, 2007), which may resemble discrete schizophrenia-like manifestations at the behavioral level.…”
Section: Introductionmentioning
confidence: 99%